Identification of replication factor C from Saccharomyces cerevisiae: a component of the leading-strand DNA replication complex. - Fien, K (1992)
A number of proteins have been isolated from human cells on the basis of their ability to support DNA replication in vitro of the simian virus 40 (SV40) origin of DNA replication. One such protein, replication factor C (RFC), functions with the proliferating cell nuclear antigen (PCNA), replication protein A (RPA), and DNA polymerase delta to synthesize the leading strand at a replication fork. To determine whether these proteins perform similar roles during replication of DNA from origins in cellular chromosomes, we have begun to characterize functionally homologous proteins from the yeast Saccharomyces cerevisiae. RFC from S. cerevisiae was purified by its ability to stimulate yeast DNA polymerase delta on a primed single-stranded DNA template in the presence of yeast PCNA and RPA. Like its human-cell counterpart, RFC from S. cerevisiae (scRFC) has an associated DNA-activated ATPase activity as well as a primer-template, structure-specific DNA binding activity. By analogy with the phage T4 and SV40 DNA replication in vitro systems, the yeast RFC, PCNA, RPA, and DNA polymerase delta activities function together as a leading-strand DNA replication complex. Now that RFC from S. cerevisiae has been purified, all seven cellular factors previously shown to be required for SV40 DNA replication in vitro have been identified in S. cerevisiae.